How foster carers experience agency support for birth family contact. Issue 1 (6th June 2019) - Collings, Susan; Wright, Amy Conley; Spencer, Margaret; Luu, Betty
Abstract: Long‐term foster carers in New South Wales, Australia, are being encouraged to consider open adoption of the child in their care. This includes an agreement to facilitate direct or face‐to‐face birth family contact without agency support. There is little Australian research on the factors that influence decisions to adopt children from out‐of‐home care. A mixed methods study was conducted to address this gap. An online survey ( n = 76) and four focus groups ( n = 30) were conducted with foster carers across New South Wales. Descriptive and thematic analysis was undertaken. Results related to birth family contact are reported. Birth family contact was an area of widespread concern among foster carers. The theme of Relationships with birth family included four subordinate themes: (a) disputed purpose, (b) supervision versus independence, (c) ambivalence about agencies, and (d) establishing boundaries. Foster carers viewed birth family contact as extremely challenging due to its effects on children and interactions with agency staff. For open adoption or guardianship to become the preferred permanency option for children over long‐term foster care, carers will need ongoing and appropriate professional support with contact.